Essential Environmental Studies - S P Misra (Ane Books, 2018)
Covers topics including natural resources (energy, land, forests, water, food), conservation, biodiversity, and pollution (air, water and soil) prevention and remediation. This book also covers social implications of pollution, environmental law and regulation, human exposure to pollutants, population growth, and sustainability.